Shaping the Future: Implementing Artificial Intelligence in the Shift to Education 4.0 - Zhang, Xue (Journal of Computer Science and Software Applications, 2021)
With the rapid advancement of the Internet and smart terminal devices, human civilization has transitioned from the 'machine industry civilization' era to the 'information intelligence civilization' era. Within the conventional educational framework, educators are tasked with both conducting scientific research and fulfilling frontline teaching responsibilities. This dual role imposes certain constraints on the exchange of information between teachers and students and hampers the advancement of educational research. Addressing the challenge of balancing these responsibilities, minimizing the hidden costs associated with teaching, and enhancing the societal benefits derived from educational research has become a critical and pressing issue. This paper explores the application of artificial intelligence in education and proposes the 'Education 4.0' model, aiming to offer innovative solutions for contemporary educational reform.